Native peroxyoxalate chemiluminescence from the reaction of bis(2,4-dinitrophenyl) oxalate and hydrogen peroxide perturbed by nonfluorophores - Capomacchia, A.C. (1987)
The reaction of bis(2,4-dinitrophenyl) oxalate and hydrogen peroxide yields an excited-state product tht luminesces with great intensity at ca. 400 nm. The weak intensity is enhanced by some agents tht normally do not fluorece. In pure solutions, the detection limits for the nonflurophores ouabain and urea, based on this effect, are 2.0 and 20 pmol, respectively.